Nickel, copper and cobalt coalescence in copper cliff converter slag - Wolf A.; Mitrašinović A.M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The aim of this investigation is to assess the effect of various additives on coalescence of nickel, copper and cobalt from slags generated during nickel extraction. The analyzed fluxes were silica and lime while examined reductants were pig iron, ferrosilicon and copper-silicon compound. Slag was settled at the different holding temperatures for various times in conditions that simulated the industrial environment. The newly formed matte and slag were characterized by their chemical composition and morphology. Silica flux generated higher partition coefficients for nickel and copper than the addition of lime. Additives used as reducing agents had higher valuable metal recovery rates and corresponding partition coefficients than fluxes. Microstructural studies showed that slag formed after adding reductants consisted of primarily fayalite, with some minute traces of magnetite as the secondary phase. Addition of 5 wt% of pig iron, ferrosilicon and copper-silicon alloys favored the formation of a metallized matte which increased Cu, Ni and Co recoveries. Addition of copper-silicon alloys with low silicon content was efficient in copper recovery but coalescence of the other metals was low. Slag treated with the ferrosilicon facilitated the highest cobalt recovery while copper-silicon alloys with silicon content above 10 wt% resulted in high coalescence of nickel and copper, 87 % and 72 % respectively.